Bowling alley bandit - Keller, Laurie (The adventures of Arnie the Doughnut, 2013)
Arnie the talking doughnut is delighted to be Mr. Bing's new pet "doughnut-dog," so when Mr. Bing starts rolling gutter balls during a big bowling tournament, Arnie suspects foul play and sets out to solve the mystery.